Psychometric Properties and Refinement of the Reproductive Coercion Scale - McCauley, Heather L. (Contraception, 2016)
OBJECTIVE: Identification and refinement of psychometric properties of the Reproductive Coercion Scale (RCS) for use in survey research and clinical practice. STUDY DESIGN: Young women ages 16–29 seeking services in 24 Pennsylvania and 5 California family planning clinics completed questionnaires. Data were pooled for analysis (n=4,674), and underlying domains were assessed using Horn’s Parallel Analysis and Exploratory Factor Analysis. Multidimensional item response theory was used to refine the scale and assess reliability and validity of a short-form RCS. RESULTS: The full, 9-item RCS had two underlying domains: pregnancy coercion and condom manipulation. Five items were retained in the short form: three about pregnancy coercion (e.g. “told you not to use birth control…”) and two for condom manipulation (e.g., “taken off the condom while you were having sex…”; one of these items is the combination of two original items on damaging the condom that were combined because of similar statistical properties and face validity and a third item on removing the condom was retained on its own). Recent reproductive coercion was reported by 6.7% and 6.3% of the sample with the full and short-form RCS, respectively. Characteristics of women reporting reproductive coercion were similar with both forms. CONCLUSION: Findings indicate that reproductive coercion includes pregnancy coercion and deliberate manipulation of condoms to promote pregnancy. Moreover, women experience RC across a continuum of severity. We selected items that varied in RC severity and discrimination to generate a 5-item short-form RCS for survey research and clinical practice.